2007
DOI: 10.1080/09546630701646156
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and quality of life of calcipotriol/betamethasone dipropionate (Dovobet®) versus calcipotriol (Daivonex®) in the treatment of psoriasis vulgaris: A randomized, multicentre, clinical trial

Abstract: Our results demonstrate a higher efficacy and more rapid onset of action with the two-compound ointment compared with calcipotriol cream alone in short-term treatment. However, sequential application of calcipotriol allows maintenance of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…The efficacy and safety of the combination of calcipotriol 50 mg/g, betamethasone dipropionate 0.5 mg/g, have been shown in previous studies (7)(8)(9)(10)(11)(12)(13)(14). The once-daily application of this combination in clinical studies on scalp psoriasis proved to be significantly superior to the individual components calcipotriol and betamethasone with respect to rapidity of effects and efficacy (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The efficacy and safety of the combination of calcipotriol 50 mg/g, betamethasone dipropionate 0.5 mg/g, have been shown in previous studies (7)(8)(9)(10)(11)(12)(13)(14). The once-daily application of this combination in clinical studies on scalp psoriasis proved to be significantly superior to the individual components calcipotriol and betamethasone with respect to rapidity of effects and efficacy (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 86%
“…This is a lipophilic gel formulation, particularly suitable for application to the scalp that combines the keratinocytes differentiation action of the vitamin D 3 analogues with the anti-inflammatory effect of steroids reducing the side-effect profile of the single topical agent. Previous studies showed the efficacy and safety of this combination in mild-to-moderate plaque-type psoriasis of body and scalp (7)(8)(9)(10)(11)(12)(13)(14). However, maintenance strategies after complete remission have been poorly investigated.…”
Section: Introductionmentioning
confidence: 97%
“…There is an ongoing need for the development of new formulations and therapeutic regimens suitable for the treatment of psoriasis. Previous reports have emphasized the high efficacy of treatments combining vitamin D analogues and corticosteroids [16]. Use of calcipotriol/betamethasone dipropionate ointment (Daivobet/Dovobet/Taclonex) in the treatment of psoriasis vulgaris is well documented [8,9,10,11,12,13,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…This combination increases the efficacy of treatment for psoriasis vulgaris, although one clinical trial showed that it may not be as effective as clobetasol, which is a superpotent class I topical steroid 3,4,16,17. The probability of a ≥75% reduction in PASI has been reported to be 47%–50% with once-daily calcipotriene + betamethasone ointment 5,18.…”
Section: Discussionmentioning
confidence: 99%